Health-related quality of life in children and adolescents with tuberous sclerosis complex and their caregivers: a multicentre cohort study from Germany - Willems, Laurent; Schubert-Bast, Susanne; Grau, Janina; Hertzberg, Christoph; Kurlemann, Gerhard; Wiemer-Kruel, Adelheid; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Fiedler, Barbara; Hahn, Andreas; Hartmann, Hans; et al. (European journal of paediatric neurology, 2021)
Objective - This study aimed to measure health-related quality of life (HRQOL) in children and adolescents with tuberous sclerosis complex (TSC) and quality of life (QOL) and depressive symptoms among caregivers. - Methods - Adequate metrics were used to assess HRQOL in children and adolescents with TSC (4-18 years, KINDLR) as well as QOL (EQ-5D) and symptoms of depression (BDI-II) among caregivers. Predictors for reduced HRQOL and depressive symptoms were identified by variance analysis, ordinal regression, and bivariate correlation. - Results - The mean HRQOL score was 67.9 ± 12.7, and significantly lower values were associated with increasing age, attending special needs education, TSC-associated psychiatric symptoms, and drug-related adverse events. The mean QOL of caregivers was 85.4 ± 15.7, and caregiver's sex, TSC mutation locus, familial TSC clustering, special needs education, degree of disability, care dependency, presence of TSC-associated psychiatric symptoms, and TSC severity were significant predictors of lower QOL. Depressive symptoms were identified in 45.7% of caregivers, associated with female sex of the caregiver, familial TSC clustering, special needs education, and presence of TSC-associated psychiatric symptoms of the child. Multivariate regression analysis revealed adolescence and drug-related adverse events as significant predictors for lower HRQOL in TSC children, and TSC2 variants predicted lower QOL and depressive symptoms in caregivers. - Conclusion - Compared with other chronic diseases, such as headache, diabetes or obesity, children with TSC have significantly lower HRQOL, which further decreases during adolescence. A decreased HRQOL of patients correlates with a lower QOL and increased symptoms of depression of their caregivers. These results may improve the comprehensive therapy and care of children and adolescents with TSC and their families and caregivers. - Trial registration - DRKS, DRKS00016045. Registered 01 March 2019, http://www.drks.de/DRKS00016045.
Gesehen am 29.01.2022